Tool Wear Evaluation of Selected Inserts after Turning by Electron Microscopy - Naprstkova, Natasa; Cais, Jaromir; Kraus, Pavel; Van, Tuong Nguyen (Manufacturing Technology Journal, 2016)
Using of cutting inserts is currently a normal part of the manufacturing process. The article deals with the tool wear evaluation of selected inserts for turning by electron microscopy. Use of electron microscopy helps on closer analysis of machining consequences forthese plates, because the microscope images captured with electronmicroscope have a greater depth of sharpness and can display examined object with greater plasticity. It is yet another way to explore objects and extends the possibilities for obtaining large quantities of information. These analyzes were realized in other experiments performed at the Faculty of Production Technology and Management of Jan Evangelisty Purkyne University in Usti nad Labem. As a experimental material the hardened steel class 16 343 according to CSN 41 0002 has been machining.
Keywords: cutting insert; tool wear; SEM